2022
DOI: 10.1088/2043-6262/ac498d
|View full text |Cite
|
Sign up to set email alerts
|

Envirronmentally friendly fabrication of Fe2TiO5-TiO2 nanocomposite for enhanced photodegradation of cinnamic acid solution

Abstract: In this study, Fe2TiO5-TiO2 heterostructured composites (FTO-Ti) were synthesised via a simple combination of the sol-gel and hydrothermal methods in a neutral medium of water. Various techniques were used to investigate the characteristics of the FTO-Ti samples, including X-ray diffraction (XRD), Raman spectroscopy, Fourier transform infrared spectroscopy (FTIR), Brunauer-Emmett-Teller adsorption (BET), scanning electron microscopy (SEM), transmission electron microscopy (TEM), UV-Vis diffuse reflectance spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…In some studies, TiO 2 was combined with pseudobrookites such as Fe 2 TiO 5 , or Al 2 TiO 5 to construct heterostructure photocatalysts having high efficiency. In this work, the type-II heterojunction Fe 2 TiO 5 /TiO 2 was synthesized by carbon templates and ion adsorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, TiO 2 was combined with pseudobrookites such as Fe 2 TiO 5 , or Al 2 TiO 5 to construct heterostructure photocatalysts having high efficiency. In this work, the type-II heterojunction Fe 2 TiO 5 /TiO 2 was synthesized by carbon templates and ion adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…The hollow nanosphere had a high surface area of 220 m 2 /g and its photocatalytic activity was three times that of P25 in the degradation of rhodamine B. Meanwhile, Fe 2 TiO 5 /TiO 2 25 and Al 2 TiO 5 /TiO 2 26 heterostructures were synthesized via a simple combination of sol–gel and hydrothermal methods in a neutral medium of water. It was found that compared to TiO 2 , the combination of TiO 2 with Fe 2 TiO 5 and Al 2 TiO 5 has significantly reduced the crystal and particle size, increased the surface area, simultaneously reduced the band gap energy of the catalyst, and extended the region of the photon absorption zone toward visible waves (407 vs 395 nm).…”
Section: Introductionmentioning
confidence: 99%